Disentangling the immune response and host-pathogen interactions in Francisella noatunensis infected Atlantic cod - Solbakken, Monica Hongrø; Jentoft, Sissel; Reitan, Trond; Mikkelsen, Helene; Gregers, Tone Fredsvik; Bakke, Oddmund; Jakobsen, Kjetill Sigurd; Seppola, Marit (Comparative Biochemistry and Physiology Part D: Genomics and Proteomics, 2019)
The genetic repertoire underlying teleost immunity has been shown to be highly variable. A rare example is Atlantic cod and its relatives Gadiformes that lacks a hallmark of vertebrate immunity: Major Histocompatibility Complex class II. No immunological studies so far have fully unraveled the functionality of this particular immune system. Through global transcriptomic profiling, we investigate the immune response and host-pathogen interaction of Atlantic cod infected with the facultative intracellular bacterium Francisella noatunensis. We find that Atlantic cod displays an overall classic innate immune response with inflammation, acute-phase proteins and cell recruitment through up-regulation of e.g. IL1B, fibrinogen, cathelicidin, hepcidin and several chemotactic cytokines such as the neutrophil attractants CXCL1 and CXCL8. In terms of adaptive immunity, we observe up-regulation of interferon gamma followed by up-regulation of several MHCI transcripts and genes related to antigen transport and loading. Finally, we find up-regulation of immunoglobulins and down-regulation of T-cell and NK-like cell markers. Our analyses also uncover some contradictory transcriptional findings such as up-regulation of anti-inflammatory IL10 as well as down-regulation of the NADPH oxidase complex and myeloperoxidase. This we interpret as the result of host-pathogen interactions where F. noatunensis modulates the immune response. In summary, our results suggest that Atlantic cod mounts a classic innate immune response as well as a neutrophil-driven response. In terms of adaptive immunity, both endogenous and exogenous antigens are being presented on MHCI and antibody production is likely enabled through direct B-cell stimulation with possible neutrophil help. Collectively, we have obtained novel insight in the orchestration of the Atlantic cod immune system and determined likely targets of F. noatunensis host-pathogen interactions.